Paradigma Pai Rahmatan Lil Alamin Dalam Ragam Perspektif - Sahrul Takim; Adiyana Adam; Tamsin Yoioga (Peneliti.net, 2022)
This principle of the Qur'an in its grounding level has experienced the opposite image. Islam as a religion is often accused of being a source of conflict with religious nuances. Why do acts of violence [terror or destruction] against ideologically different groups always use religious normative arguments to justify that the acts of violence they commit are scientifically correct? This paper starts with the problem, namely what is the concept of Teo-homo Ecosystem, what is the concept of Prosperity and Welfare?, What is Af'alu Al-Khmsa and Human Rights like? And How Are the Four Pillars Towards Rahmatan Lil Alamin (Science, Superior Humanity, Faith-Islam and Ikhsan, A Just Social System)? The results of the study show that the Islamic idea of ​​peace is a very basic and deep thought because it is closely related to the character of the Islamic religion, and is even a universal Islamic thought about nature, life, and humans. This ukhuwwah prioritizes common ground and distances points of difference in order to create a harmonious, safe, serene, and peaceful life (rahmatan lil 'alamîn).